Harmonizing Arbitration: Clarity, Consistency, and Consent in the Application of Ex Aequo Et Bono - Hadylaya, Michael Herdi (Universitas Negeri Gorontalo, 2024)
This article delves into the intricate dynamics surrounding the application of the ex aequo et bono principle in arbitration, addressing concerns arising from potential procedural challenges and deviations from justice principles amid the escalating popularity of arbitration. The study intricately navigates the legal complexities of this principle, centering on the interpretation of Article 56 of Law 30/1999. Specifically, it scrutinizes whether the article mandates parties' consent for the arbitrator to decide based on ex aequo et bono. Employing a normative legal research approach and utilizing legal hermeneutics with a structuralist focus, the research analyzes the interplay of written agreements, tacit understandings, and standard practices in arbitration. The article underscores the critical role of precise protocols and unequivocal agreements in safeguarding the integrity and effectiveness of the arbitration process. It highlights the paramount need for clarity and consistency in legal provisions, advocating for collaborative efforts between legal authorities and arbitration institutions. This collaboration is essential for aligning statutory provisions and arbitration rules, ultimately fortifying a robust and dependable framework for the equitable resolution of conflicts. In conclusion, the article calls for a harmonized approach to address inconsistencies, enhance the legitimacy of arbitration decisions, and foster trust in the arbitration process. By exploring these challenges, the article contributes to the ongoing discourse of optimizing arbitration as a fair and efficient means of resolving international disputes.